2018
DOI: 10.1373/clinchem.2017.282517
|View full text |Cite
|
Sign up to set email alerts
|

Biological Variation of Creatinine, Cystatin C, and eGFR over 24 Hours

Abstract: Despite differences in CV of creatinine, the CV and RCV of the eGFR equations were relatively similar for people with or without CKD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(51 citation statements)
references
References 38 publications
(49 reference statements)
4
42
5
Order By: Relevance
“…This change is in accordance with findings in other study populations exposed to heat stress such as sugarcane workers [31,32] and athletes in endurance competitions [33], but not under sedentary conditions [34]. Authors considered as potential mechanisms for the kidney function decrease observed in these investigations dehydration, volume depletion, rhabdomyolysis, systemic inflammation, and oxidative stress triggered by environmental heat and the extreme physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…This change is in accordance with findings in other study populations exposed to heat stress such as sugarcane workers [31,32] and athletes in endurance competitions [33], but not under sedentary conditions [34]. Authors considered as potential mechanisms for the kidney function decrease observed in these investigations dehydration, volume depletion, rhabdomyolysis, systemic inflammation, and oxidative stress triggered by environmental heat and the extreme physical activity.…”
Section: Discussionsupporting
confidence: 90%
“…It could be argued that our results are caused by fluctuations of serum creatinine levels that are not due to changes in renal function. However, Hilderink et al showed that this spontaneous variability leads to fluctuations of eGFR of 13-20% 29 only, a value lower than many of our criteria used to define a group of individuals with a detrimental prognosis. Nonetheless we could not evaluate the stability of an eGFR decline of ≥ 45 or 50% as the patient number became low.…”
Section: Discussionmentioning
confidence: 57%
“…It provides the estimated glomerular filtration rate and is based on the child's height and values of serum creatinine, a by‐product of muscle metabolism eliminated through glomerular filtration . Unfortunately, estimated glomerular filtration rate and serum creatinine are both unreliable and inaccurate markers for monitoring of kidney function and detecting KI in pediatric populations for the following reasons: (1) approximately 50% of renal parenchymal loss must occur before serum creatinine changes can be detected; (2) serum creatinine can be influenced by muscle mass variation, nutrition, age, and sex; (3) during the first days of life, serum creatinine rather reflects the maternal kidney function instead of the kidney function of the neonate; (4) overestimation of kidney function is possible in patients with cachexia; and (5) serum creatinine does not allow the exact localization nor the extent of KI …”
Section: Overview Of Kidney Injury Biomarkers For Detecting Drug‐relamentioning
confidence: 99%
“…10 Unfortunately, estimated glomerular filtration rate and serum creatinine are both unreliable and inaccurate markers for monitoring of kidney function and detecting KI in pediatric populations for the following reasons: (1) approximately 50% of renal parenchymal loss must occur before serum creatinine changes can be detected; (2) serum creatinine can be influenced by muscle mass variation, nutrition, age, and sex; (3) during the first days of life, serum creatinine rather reflects the maternal kidney function instead of the kidney function of the neonate; (4) overestimation of kidney function is possible in patients with cachexia; and (5) serum creatinine does not allow the exact localization nor the extent of KI. [11][12][13][14][15][16][17][18][19][20][21][22][23] Understanding Age-Dependent Changes in Pediatrics Kidney function comprises 3 main processes: First, glomerular filtration is responsible for the filtration of the plasma across the glomerular membrane into the renal tubule. Second, tubular excretion transporters can increase the excretion of drug molecules by more actively transport from the plasma into the tubule.…”
mentioning
confidence: 99%